The Effect of School Leadership and Teacher Training on Teacher Performance at Senior High School 1 Tondon North Toraja District - Yerma Yerni Timang; Mesta Limbong; Ied V. R. Sitepu (CV. Creative Tugu Pena, 2021)
The article was to analyse the teacher teaching performance, principal leadership, and teacher training at Senior High School 1 Tondon North Toraja District, to analyze the influence of the principal's leadership on the teaching performance of teachers, and the effect of teacher training on teacher teaching performance, and the influence of principal leadership and teacher training on teacher teaching performance. The researchers used a quantitative method with an associative research approach to causal relationships. The samples were obtained using saturated sampling (census). The data was obtained through a research instrument in the form of a questionnaire. The correlation analysis data showed that there was a positive effect of teacher training on teacher teaching performance at SMPN 1 Tondon, North Toraja Regency. The value of the derivation coefficient between the 2 variables was 0.850 or 85.0%. That was, the teacher training variable was able to explain the variation in teacher teaching performance variables 85.0%. The results of simple regression analysis showed that teacher training has a significant and positive effect on teacher teaching performance at SMPN 1 Tondon, North Toraja Regency. It means that if teacher training improves, teacher teaching performance will be increase. Keywords: Teachers’ Leadership,, Teacher Teaching Performance, School Leadership